Mechanisms and kinetic studies of OH-initiated atmospheric oxidation of methoxyphenols in the presence of O2 and NOx. Issue 39 (25th September 2019) - Sun, Yanhui; Xu, Fei; Li, Xiaofan; Zhang, Qingzhu; Gu, Yuanxiang
Abstract : Methoxyphenols, as the main products and tracers of biomass burning, have been demonstrated to play an important role in the formation of secondary organic aerosols. Abstract : Methoxyphenols, as the main products and tracers of biomass burning, have been demonstrated to play an important role in the formation of secondary organic aerosols. However, their chemical transformation and migration in the atmosphere haven't been well characterized. In this study, detailed gas-phase reaction mechanisms and kinetics of three representative methoxyphenols (guaiacol, creosol and syringol) with OH radicals were investigated by using density functional theory (DFT). The initial reactions of methoxyphenols with OH radicals proceed via two different patterns, including OH-addition and H-atom abstraction. Subsequent reaction schemes of the active intermediates in the presence of O2 /NO x are thoughtfully modeled. Catechol, methyl glyoxylate, malealdehyde and carbonyl or carboxyl compounds were confirmed as the dominant oxidation products for guaiacol. As a supplementary study, the formation pathways for the expected products nitroguaiacol and nitrocatechol were presented in high-NO2 conditions. Total and individual rate coefficients are calculated using the MESMER program at 294 K and 1 atm. The lifetimes of guaiacol, creosol and syringol were estimated to be 4.27, 3.56 and 2.98 hours, respectively, which are strongly competitive with the solar photolysis of methoxyphenols.